2017
DOI: 10.1186/s12985-017-0790-9
|View full text |Cite
|
Sign up to set email alerts
|

Variability in P1 gene redefines phylogenetic relationships among cassava brown streak viruses

Abstract: BackgroundCassava brown streak disease is emerging as the most important viral disease of cassava in Africa, and is consequently a threat to food security. Two distinct species of the genus Ipomovirus (family Potyviridae) cause the disease: Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV). To understand the evolutionary relationships among the viruses, 64 nucleotide sequences from the variable P1 gene from major cassava producing areas of east and central-southern Africa were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…However, primers based on HAM1 and CP may provide a very robust tool for general screening of CBSV for breeders, when there is no need to distinguish the strains or variants within CBSV clades. It was observed that HAM1 and CP were the most conserved genes between CBSV clades 1 and 2, in contrast to P1, which was the most variable gene, consistent with the observations of Mbewe et al (2017). The high conservation of HAM1 and CP among isolates of CBSV clades 1 and 2 observed here suggests that both were maintained during speciation within CBSV.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, primers based on HAM1 and CP may provide a very robust tool for general screening of CBSV for breeders, when there is no need to distinguish the strains or variants within CBSV clades. It was observed that HAM1 and CP were the most conserved genes between CBSV clades 1 and 2, in contrast to P1, which was the most variable gene, consistent with the observations of Mbewe et al (2017). The high conservation of HAM1 and CP among isolates of CBSV clades 1 and 2 observed here suggests that both were maintained during speciation within CBSV.…”
Section: Discussionsupporting
confidence: 89%
“…The two clades of CBSV have been previously reported, based on the P1 gene sequences (Mbewe et al ., ) and WGSs (Alicai et al ., ). This study presents molecular evidence that among the 10 gene sequences of CBSV, eight can be used to discriminate the two clades.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For convenience, we refer to the first class as the Common Class, since there is no significant divergence among any of the taxa; we refer to the second class as the UCBSV Class, since this class is characterised by the divergence between the CBSV and UCBSV replicates; and we refer to the third class as the CBSV-TZ Class. The reason for this is that the four CBSV replicates that diverge from the remainder in this class are also present in the study of the P1 gene (Mbewe et al, 2017) referred to earlier. These four replicates are found in the third clade which they tentatively labelled CBSV-TZ, and so it seems probable that the phylogenetic signal captured in the third class is related to the divergence of CBSV-TZ from CBSV.…”
Section: Resultsmentioning
confidence: 93%
“…This is not straightforward though, as it has already been shown that these viruses are fast-evolving (CBSV moreso than UCBSV) (Alicai et al, 2016). Mbewe et al (2017) showed that in the gene tree of the P1 gene, a third distinct clade is found in addition to CBSV and UCBSV, which they tentatively labelled Tanzanian CBSV (CBSV-TZ). Critical to winning the fight against CBSD is ongoing research into the evolutionary forces acting on these viruses, at both the molecular level and geographically.…”
Section: Introductionmentioning
confidence: 99%